MULTIPLE SIBLINGS' EXPERIENCES OF THEIR ELDERLY PARENT'S DEATH: A QUALITATIVE ANALYSIS. (11th November 2018) - Moss, M; Moss, S
Abstract: We examined how siblings (a brother and a sister) in each of 6 bereaved families compared in their bereavement experience after the death of their elderly father. Families were a sub-group of 34 bereaved families in an ethnographic study: The Meaning of the Death of the First Elderly Parent: A Family Perspective (NIH, R01AG031806). Each sibling in each family completed two separate fully transcribed ethnographic interviews (averaging over 3 hours). We explore complex ways that brothers and sisters (mean age 52) had both congruent and diverse responses to their father's (mean age 82) death. Our analytic themes demonstrate how the value of a with-in family research approach can increase understanding of complex patterns of bereavement within a family. Findings: Although the siblings described much of the end of life and cause of death in similar ways, the meanings and impact of the death often differed. In most every family, we found that siblings differed in the quality of the relationship with the father, their unique life-course experiences, impact of father's death on sense of personal identity, child's view of the widowed mother, perceived central themes in family ties, and impact of father's death on future sibling ties. Discussion examines the role of sibling gender and the differential impact of each sibling's world view on his/her bereavement. Future research cannot assume that the reaction of one sibling to his/her parent's death represents that of other bereaved siblings.